Deciphering belowground nitrifier assemblages with elevational soil sampling in a subtropical forest ecosystem (Mount Lu, China). Issue 1 (9th December 2019) - Han, Shun; Tan, Shuang; Wang, Achen; Chen, Wenli; Huang, Qiaoyun
ABSTRACT: The elevational distribution patterns of microbial functional groups have long been attracting scientific interest. Ammonia-oxidizers (ammonia-oxidizing archaea [AOA] and bacteria [AOB]), complete ammonia oxidation (comammox) Nitrospira and nitrite-oxidizers (e.g. Nitrobacter and Nitrospira ) play crucial roles in the nitrogen cycle, yet their activities and abundances in response to elevational gradients in a subtropical forest ecosystem remain unclear. Here, we investigated the distribution of potential functions and abundances of these nitrifiers in forest soils along elevational gradients on Mount Lu, China. Our results showed that AOA and Nitrospira abundance was higher than that of their counterparts. Only AOA, Nitrobacter and comammox Nitrospira abundances followed a hump-backed-model with altitude. Soil potential ammonia-oxidation activity (PAO) and nitrite-oxidation activity (PNO) ranged from 0.003 to 0.084 and 0.34 to 0.53 μg NO2 − -N g −1 dry soil h −1, respectively. The biotic (AOA, Nitrobacter, Nitrospira and comammox Nitrospira abundances) and abiotic factors (soil variables) jointly affected PAO, whereas the abiotic factors were mainly responsible for PNO. Variance partitioning analysis showed that contemporary environmental disturbance is the most important driver for the biogeography of nitrifier assemblages. Overall, our findings indicate that forest soil nitrifier assemblages exhibit a biogeographic pattern largely shaped by soil chemistry along an elevational gradient. Abstract : Soil nitrifier assemblages exhibit biogeographic patterns shaped more by soil variables than by elevational gradients.